2014
DOI: 10.1002/mrc.4082
|View full text |Cite
|
Sign up to set email alerts
|

HR‐MAS NMR metabolomics of ‘Swingle’ citrumelo rootstock genetically modified to overproduce proline

Abstract: The accumulation of proline is a typical physiological response to abiotic stresses in higher plants. 'Swingle' citrumelo, an important rootstock for citrus production, has been modified with a mutated Δ 1 -pyrroline-5-carboxylate synthetase gene (VaP5CSF129A) linked to the cauliflower mosaic virus 35S promoter to induce the overproduction of free proline. This paper presents a comparative metabolomic study of nontransgenic versus transgenic 'Swingle' citrumelo plants with high endogenous proline. 1 H high-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Mucci et al studied different tissues of lemons and citrons to understand the similarities and the differences between these two fruits [57]. In addition, it is possible to use metabolic profiling to characterise newly discovered plants [58,59] or mutants of plants [39,60,61]. The geographical origin of sweet peppers [62], garlic [63] and cocoa beans [64] has been investigated with HR-MAS NMR.…”
Section: Applications Of Hr-mas Nmr In Plant Metabolomicsmentioning
confidence: 99%
“…Mucci et al studied different tissues of lemons and citrons to understand the similarities and the differences between these two fruits [57]. In addition, it is possible to use metabolic profiling to characterise newly discovered plants [58,59] or mutants of plants [39,60,61]. The geographical origin of sweet peppers [62], garlic [63] and cocoa beans [64] has been investigated with HR-MAS NMR.…”
Section: Applications Of Hr-mas Nmr In Plant Metabolomicsmentioning
confidence: 99%
“…Moreover, the authors also reported an overexpression of quercetin and myricetin flavonoids in the transgenic beans. Roots and leaves of swingle citrumelo were investigated to prove the capability of a selected transgene to induce an overexpression of proline, an amino acid commonly associated with plant responses to certain environmental stress [50]. In particular, the authors used HRMAS to compare the metabolome of wild-type plants with that of transgenic T-35S plants carrying the VaP5CSF129A transgene encoding a mutated enzyme involved in proline biosynthesis.…”
Section: Plantsmentioning
confidence: 99%
“…In particular, the authors used HRMAS to compare the metabolome of wild-type plants with that of transgenic T-35S plants carrying the VaP5CSF129A transgene encoding a mutated enzyme involved in proline biosynthesis. Spectroscopic results showed that the transgenic plants exhibited a genotype-dependent response that entailed different levels of proline, proline betaine, sucrose, and acetic acid [50]. In another study, the composition of wild-type Arabidopsis thaliana was compared to that of cellulose-deficient mutant ectopic lignification1 through HRMAS-based experiments.…”
Section: Plantsmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) is a versatile technique in the study of small molecules and has been useful in several metabolomic studies . NMR combined with chemometrics has supported the investigation of biological systems under various conditions, in both animals and plants …”
Section: Introductionmentioning
confidence: 99%